STATE OWNED ENTERPRISES AND CAPITAL MARKET IN CIS COUNTRIES - Otabek Narziev (Scholar Express Journals, 2022)
In CIS countries the state actively participates in securities market relations through its SOEs and banks that issue, own and manage various securities, and render intermediary services in the securities market. The state sets rules to regulate market relations through authorized bodies that are also responsible for the fairness of dispute resolution. Consequently, a high level of direct and indirect state participation in securities market relations suggests the prevalence of general administrative principles over market principles. In such conditions, one of the main tasks of implementing market principles in the securities market, and respectively improve equity financing, would be to consider the reduction of state share and administrative methods. For this, it is necessary to hold extensive and comprehensive reforms that are underpinned by sound theory to get proper understanding and direction. In this regard, this chapter provides an outline of the theoretical bases of state participation in the economy, an overview of the state’s role and the extent of state ownership, an analysis of the main SOE problems, and provides perspectives of future SOE reforms in selected CIS countries
Keywords: SOEs; POEs; capital market; CIS countries